Validasi Metode Analisis Penetapan Kadar Protein Ekstrak Ikan Gabus dengan Metode Lowry dan Bromocresol Green - Suhendi, Andi; Rohman, Abdul; Cahyaningrum, Safira (Jurnal Kefarmasian Indonesia, 2023)
Snakehead fish is one of the biological resources with high economic value because it contains high albumin levels. Analytical methods for the determination of protein content in snakehead fish are available not been validated. This study aims to obtain a comparison of the accuracy, repeatability, intermediate precision, and linearity between the Lowry and Bromocresol-green methods in determining albumin levels from snakehead fish extracts. This study was performed with the SHIMADZU UV-1280 spectrophotometer at a wavelength of 778 nm for the lowry method and 638 nm for the bromocresol-green method. The results of the study show that all parameters meet the requirements for accepting validation. The results were tested statistically with the independent t-test, the p-value was 0.172 (p> 0.05) the accuracy between the Lowry and Bromocresol-green methods did not have a significant difference, that the Lowry and Bromocresol green methods had the same ability to determine accuracy parameters and precision parameters, the p-value is 0.000 (p